2019
DOI: 10.1111/papr.12846
|View full text |Cite
|
Sign up to set email alerts
|

Domains of Chronic Low Back Pain and Assessing Treatment Effectiveness: A Clinical Perspective

Abstract: Nonspecific chronic low back pain (CLBP) is a common clinical condition that has impacts at both the individual and societal level. Pain intensity is a primary outcome used in clinical practice to quantify the severity of CLBP and the efficacy of its treatment; however, pain is a subjective experience that is impacted by a multitude of factors. Moreover, differences in effect sizes for pain intensity are not observed between common conservative treatments, such as spinal manipulative therapy, cognitive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 166 publications
(206 reference statements)
0
99
1
12
Order By: Relevance
“…19,20 Currently, only 2 published papers looked at all 3 physical function measures within 1 study and found support for an association between PROs and performance-based function but little or no support for associations with step-count. 21,22 Treatments aimed at improving physical function in chronic pain typically target psychosocial factors such as pain, coping, and social-emotional factors, [23][24][25] which are associated with improvement in PROs. 8,26 However, it is unclear whether targeting these constructs also improves performance-based and objective/ambulatory-measured physical function, as prior studies found mixed results for associations with performance-based physical function 21,27,28 and step-count physical function.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Currently, only 2 published papers looked at all 3 physical function measures within 1 study and found support for an association between PROs and performance-based function but little or no support for associations with step-count. 21,22 Treatments aimed at improving physical function in chronic pain typically target psychosocial factors such as pain, coping, and social-emotional factors, [23][24][25] which are associated with improvement in PROs. 8,26 However, it is unclear whether targeting these constructs also improves performance-based and objective/ambulatory-measured physical function, as prior studies found mixed results for associations with performance-based physical function 21,27,28 and step-count physical function.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of years lived with disability burden pattern there is similar pattern in 1990 to 2010 with lower back pain being most likely cause of musculoskeletal disability [1]. Various biopsychosocial factors lead to disability in chronic back pain [13,14]. Degenerative disc disease is a leading cause of lower back pain on a global scale [15].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common musculoskeletal problems is low back pain, which affects people's quality of life [1]. Non-specific low back pain is the main cause of back pain; however; low back pain is usually caused by disc herniation, lumbar stenosis, trauma, muscle strain, lumbar spondylosis, spine and kidney infections, certain cancers, endometriosis, arthritis, and ankylosing spondylitis [2,3].…”
Section: Introductionmentioning
confidence: 99%